IDENTIFIKASI BANGUNAN KUMUH YANG MEMPENGARUHI KUALITAS LINGKUNGAN PERMUKIMAN TAMANSARI KOTA BANDUNG - Febrion, Churchil; Wijaya, Karto; Sugandi, Dedi (Jurnal Arsitektur ARCADE, 2020)
The density of urban settlements has resulted in poor visualization of the city, the need to improve the quality of buildings and rearrangement of the area which aims to improve the quality of visualization of the face of the city of Bandung for the better. Moreover, the area is located near one of Bandung's landmarks, namely the Pasopati bridge which is also an access to the city of Bandung. The high price of land and building materials causes a very dense residential environment, every existing land will be built as much as possible with bad construction values, of the many slum settlements in Bandung City, Tamansari is one of the settlements that are still slum. The buildings in the Tamansari area have various forms, the building area is relatively narrow and the material is minimal, and the construction is minimal. The tightness of the building distance makes road access in this area very narrow so that it cannot be used for evacuation routes and other emergency routes, another result of the density of the building is a lack of green open space or public facilities. This is what makes the visualization of this area worse and if you look at it from above the Pasopati bridge. The Pasopati Bridge is a bridge that stretches over this village and has become one of the city's icons, a bridge that connects the Pasteur area which is one of the access points to Bandung City to the center of Bandung City and across an area that has history and has even become an icon of the city of Bandung, namely Satay tower. This makes observers interested in researching slum buildings that have been built for a long time. The purpose of this study is to determine the level of slums on the banks of the Cikapundung river which is clearly visible from the bridge which is the access to the city gate of Bandung.